2017
DOI: 10.1097/eja.0000000000000668
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane attenuates systemic inflammation compared with propofol, but does not modulate neuro-inflammation

Abstract: Animal approval No. 134/2014, Veterinäramt Zürich.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…Our comparison of propofol- and isoflurane-treated patients was limited by slight differences in age, hydromorphone dose, and BIS index (Table 1 ), though we believe that these slight differences between groups are unlikely to have obscured a biologically significant difference in cytokines levels. Our results are similar to those of Beck-Schimmer et al, who recently found no difference in LPS-induced neuroinflammation among rats treated with propofol vs. the inhaled anesthetic sevoflurane ( 26 ). However, due to insufficient prior literature comparing the human postoperative increase in CSF cytokines between propofol- vs. isoflurane-treated patients, we were unable to perform an a priori sample size calculation for this study.…”
Section: Discussionsupporting
confidence: 92%
“…Our comparison of propofol- and isoflurane-treated patients was limited by slight differences in age, hydromorphone dose, and BIS index (Table 1 ), though we believe that these slight differences between groups are unlikely to have obscured a biologically significant difference in cytokines levels. Our results are similar to those of Beck-Schimmer et al, who recently found no difference in LPS-induced neuroinflammation among rats treated with propofol vs. the inhaled anesthetic sevoflurane ( 26 ). However, due to insufficient prior literature comparing the human postoperative increase in CSF cytokines between propofol- vs. isoflurane-treated patients, we were unable to perform an a priori sample size calculation for this study.…”
Section: Discussionsupporting
confidence: 92%
“…17 In a lipopolysaccharide-induced sepsis model in rats, concentrations of MCP-1, interleukin-6, and cytokine-induced neutrophil chemoattractant protein-1 measured 3, 6, and 12 h after lipopolysaccharide infusion were lower in sevoflurane-treated rats compared with propofol-treated rats. 18 Koutsogiannaki and colleagues 19 showed that improved survival in sevoflurane-treated mice subjected to sepsis was associated with less apoptosis in the spleen. Sevoflurane reduced neutrophil apoptosis by a Fas death domain-Fas-associated death domain interaction.…”
Section: Potential Beneficial Effects Of Volatile Anaesthetics In Covmentioning
confidence: 99%
“…In a randomized controlled multicentre trial of Beck et al with 460 patients addressing the effect of volatile versus intravenous anaesthetics on major complications after lung surgery no difference between the two anaesthesia regimens was evident (19,20). Importantly inhalational anaesthetics dose-dependently influence local inflammatory processes, partially reverse hypoxic pulmonary vasoconstriction and reduce alveolar clearance (19,21).…”
Section: Anaestheticsmentioning
confidence: 99%